Icariin protects against cage layer osteoporosis by intervening in steroid biosynthesis and glycerophospholipid metabolism - Zhengwang Yu; Jie Huang; Zhongxin Zhou (BMC, 2021)
Abstract Cage layer osteoporosis (CLO) is a common bone metabolism disease in the breeding industry of China. However, effective prevention for CLO has not been developed. Icariin (ICA), the main bioactive component of the Chinese herb Epimedium, has been shown to have good therapeutic effects on bone-related diseases. In this study, the effects of ICA were further evaluated in a low-calcium diet-induced CLO, and a serum metabolomics assay was performed to understand the underlying mechanisms. A total of 144 31-wk-old Lohmann pink-shell laying hens were randomly allocated to 4 groups with 6 replicates of 6 hens per replicate. The 4 dietary treatment groups consisted of a basal diet (3.5% calcium), a low-calcium diet (2.0% calcium), and a low-calcium diet supplemented with 0.5 or 2.0 g/kg ICA. The results showed that ICA exerted good osteoprotective effects on low-calcium diet-induced CLO. ICA significantly increased femur bone mineral density, improved bone microstructure, decreased bone metabolic level, and upregulated mRNA expression of bone formation genes in femoral bone tissue. Serum untargeted metabolomics analysis showed that 8 metabolite levels were significantly changed after ICA treatment, including increased contents of 7-dehydrocholesterol, 7-oxocholesterol, desmosterol, PC (18:1(9Z)/18:1(9Z)), PS (18:0/18:1(9Z)), N,N-dimethylaniline and 2-hydroxy-butanoic acid and decreased N2,N2-dimethylguanosine. Metabolic pathway analysis based on the above 8 metabolites indicated that ICA mainly perturbed steroid biosynthesis and glycerophospholipid metabolism. These findings suggest that ICA can effectively prevent bone loss in low-calcium diet-induced CLO by mediating steroid biosynthesis and glycerophospholipid metabolism and provide new information for the regulation of bone metabolic diseases.